Preexisting Type 1 Diabetes Mellitus Blunts the Development of Posttraumatic Osteoarthritis. (19th April 2022) - Rios‐Arce, Naiomy D; Murugesh, Deepa K; Hum, Nicholas R; Sebastian, Aimy; Jbeily, Elias H; Christiansen, Blaine A; Loots, Gabriela G
ABSTRACT: Type 1 diabetes mellitus (T1DM) affects 9.5% of the population. T1DM is characterized by severe insulin deficiency that causes hyperglycemia and leads to several systemic effects. T1DM has been suggested as a risk factor for articular cartilage damage and loss, which could expedite the development of osteoarthritis (OA). OA represents a major public health challenge by affecting 300 million people globally, yet very little is known about the correlation between T1DM and OA. In addition, current studies that have looked at the interaction between diabetes mellitus and OA have reported conflicting results with some suggesting a positive correlation whereas others did not. In this study, we aimed to evaluate whether T1DM exacerbates the development of spontaneous OA or accelerates the progression of posttraumatic osteoarthritis (PTOA) after joint injury. Histological evaluation of T1DM and control joints determined that T1DM mice displayed cartilage degeneration measurements consistent with mild OA phenotypes. RNA sequencing analyses identified significantly upregulated genes in T1DM corresponding to matrix‐degrading enzymes known to promote cartilage matrix degradation, suggesting a role of these enzymes in OA development. Next, we assessed whether preexisting T1DM influences PTOA development subsequent to trauma. At 6 weeks post‐injury, T1DM injured joints displayed significantly less cartilage damage and joint degeneration than injured non‐diabetic joints, suggesting a significant delay in PTOA disease progression. At the single‐cell resolution, we identified increased number of cells expressing the chondrocyte markers Col2a1, Acan, and Cytl1 in the T1DM injured group. Our findings demonstrate that T1DM can be a risk factor for OA but not for PTOA. This study provides the first account of single‐cell resolution related to T1DM and the risk for OA and PTOA. © 2022 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research.